Genetic Diversity in Leatherback Turtles (Dermochelys coriacea) along the Andaman Sea of Thailand - Chutima Wongfu; Wareerat Prasitwiset; Anocha Poommouang; Kittisak Buddhachat; Janine L. Brown; Siriwadee Chomdej; Jatupol Kampuansai; Patcharaporn Kaewmong; Kongkiat Kittiwattanawong; Korakot Nganvongpanit (Diversity, 2022)
The leatherback sea turtle (Dermochelys coriacea) is the largest and one of the most migratory turtle species, inhabiting oceans throughout the world. There has been a steady decline in leatherback populations over the past several decades due to human activities. They are considered endangered in Thailand and global, so conservation strategies are needed to study and protect the species, including determining their genetic diversity. A total of 8 microsatellite loci and 658 bp amplicon of mitochondrial DNA (mtDNA) were used to assess genetic data from 149 dead leatherback turtle hatchlings among 14 nests in five locations along the Andaman Sea, Thailand, between 2018–2020. The microsatellite findings show that the observed heterozygosity (Ho) ranged from 0.44 ± 0.09 to 0.65 ± 0.10. Population structures were further divided into two genetically distinct groups by Bayesian inference. For the mtDNA control region, our samples consisted of three haplotypes. Globally, there are 27 haplotypes of leatherback turtles, with a relatively low genetic diversity (h = 0.43). These results reveal the genetic status of leatherback turtles in Thailand and globally, and raise concerns about their relative genetic health, which highlight the need for proactive, long-term management and conservation strategies for this endangered species.